Oral squamous cell carcinoma in the Sudan: clinical behavior, DNA ploidy and S-phase fraction characteristics - Yousif Eltohami; Osama Eltayeb; Ahmed Suleiman (BMC Oral Health)
Abstract Background The DNA ploidy and the S phase fraction (SPF) are associated with advanced tumors progression. The present study aimed to investigate the clinicopathological behavior of oral squamous cell carcinoma(OSCC) and the prognostication of the DNA ploidy and the SPF on its clinical outcomes. Methods This a prospective longitudinal study of 93 OSCC patients (186 specimens). Using high resolution flowcytometry, DNA analysis and SPF were performed for the primary tumor, field of cancerization and a control normal field. The patients were followed clinically for the development of recurrence or second primary tumor(SPT). Results All the 93 patients are associated with wide field of cancerization. Out of the total number of cases, 28 (30%) patients developed recurrence. Of them 17 (18.3%) had regional recurrence, and eight (8.6%) had local recurrence. Second primary tumors were identified in 14 (15.1%) of the cases. Nodal metastasis, overall recurrence and SPTs were significantly associated with DNA aneuploidy and high SPF. High SPF and DNA hyperploidy showed a 28% increased risk of local recurrence (P.value = 0.032). Conclusion In a series of 93 oral cancers who had wide field of cancerization, 30% of the patients developed recurrence, and 15% developed second primary tumors. The DNA ploidy and the SPF were independent prognosticators for the prediction of OSCC outcomes.